2011
DOI: 10.1002/ar.21534
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Ultrastructural Examinations of Porcine Tonsils

Abstract: The histology and ultrastructure of porcine tonsils were studied. The porcine tonsils were lymphoepithelial organs situated at the opening of both the digestive and respiratory tracts. The tonsil of the soft palate in the oropharyngeal tract and the paraepiglottic tonsil in the laryngopharynx were mainly consisted of secondary lymphoid follicles encapsulated by connective tissue. The stratified squamous epithelia covering the tonsils and their crypts were frequently heavily infiltrated by lymphoid cells. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
(30 reference statements)
5
19
1
Order By: Relevance
“…This is in accordance with the reports of Casteleyn et al (2011) in sheep. Contrary to this, light microscopy of the tonsil of soft palate in pigs by Belz and Heath (1996) and Liu et al (2012) revealed deep crypts with distinct neck and body. In both the pseudostratified ciliated columnar and stratified squamous epithelium lined regions, the height of the reticular epithelium measured 32.27±7.92µm and 51.37±2.08µm, respectively.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…This is in accordance with the reports of Casteleyn et al (2011) in sheep. Contrary to this, light microscopy of the tonsil of soft palate in pigs by Belz and Heath (1996) and Liu et al (2012) revealed deep crypts with distinct neck and body. In both the pseudostratified ciliated columnar and stratified squamous epithelium lined regions, the height of the reticular epithelium measured 32.27±7.92µm and 51.37±2.08µm, respectively.…”
contrasting
confidence: 56%
“…In contrast, according to Belz and Heath (1996) and Liu et al (2012) in pigs and Kumar and Timoney (2006) in equines, the tonsil of soft palate was located rostrally on the oral surface of the soft palate.…”
mentioning
confidence: 90%
“…In the interfollicular and parafollicular areas meshwork of reticular and collagen fibres contained small, medium and large lymphocytes, plasma cells, macrophages, blood capillaries and HEVs (Fig.7). All these observations made in the present study tally with the reports of Belz and Heath (1996) and Liu et al (2012) in pigs and Kumar and Timoney (2006) in horse.…”
Section: Resultssupporting
confidence: 92%
“…3). Belz and Heath (1996) and Liu et al (2012) made similar observations on the morphology of the tonsils in pigs. In contrast Cocquyt et al (2005) and Yang et al (2011) observed that the tonsil of the soft palate consisted of scattered nodules of lymphoid tissue located on the dorsal (nasal) side of the soft palate in sheep and camel respectively.…”
Section: Resultssupporting
confidence: 55%
“…The tonsils of the soft palate have been recognized in many studies as the main pharyngeal mucosa-associated lymphoid tissues in swine (12,14,15,37). However, this finding might indicate that other mucosa-associated lymphoid tissues located in the oropharyngeal area, including other tonsils, play a significant role in initiating immune responses against antigens in contact with mucosal surfaces (38).…”
Section: Discussionmentioning
confidence: 99%